2010 20th International Conference on Pattern Recognition 2010
DOI: 10.1109/icpr.2010.1054
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Sleeping Posture Classification

Abstract: Sleeping posture reveals important information for eldercare and patient care, especially for bed ridden patients. Traditionally, some works address the problem from either pressure sensor or video image. This paper presents a multimodal approach to sleeping posture classification. Features from pressure sensor map and video image have been proposed in order to characterize the posture patterns. The spatiotemporal registration of the two modalities has been considered in the design, and the joint feature extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…Greater order moments increased estimation errors as reported in [8] and did not improve classification. The implementation of [9] to classify poses achieved an accuracy of 100 % in scenarios with bright and medium illumination. The performance increase (the authors reported a 94 % accuracy) is likely due to tunning parameters, higher resolution and complete bed coverage of the Tekscan mat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Greater order moments increased estimation errors as reported in [8] and did not improve classification. The implementation of [9] to classify poses achieved an accuracy of 100 % in scenarios with bright and medium illumination. The performance increase (the authors reported a 94 % accuracy) is likely due to tunning parameters, higher resolution and complete bed coverage of the Tekscan mat.…”
Section: Discussionmentioning
confidence: 99%
“…4. Confusion matrices of implemented method from [9] with 16 % and our proposed method with 70 % accuracies for dark and occluded scenarios. The confusion matrices show how the indexes of the estimated labelsl (x-axis) match the actual labels l * (y-axis).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare applications of pose monitoring include the detection and classification of sleep poses in controlled environments [14]. Static pose classification in a range of simulated healthcare environments is addressed in [15], where the authors use modality trust and RGB, Depth, and Pressure data.…”
Section: Introductionmentioning
confidence: 99%